2005
DOI: 10.1002/casp.814
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of adaptation to the euro in the Republic of Ireland: I. attitudes, the ‘euro illusion’ and the perception of prices

Abstract: This is the first of two reports of a study using semi-structured, in-depth interviews to explore the current and recollected experiences of Irish people for the period before, during, and after the introduction of euro notes and coins (1 January 2002). Twenty-four adults, 12 males and 12 females, covering a range of ages and educational attainment, were interviewed between October 2002 and February 2003. We found that most had welcomed the new currency initially, though some had felt less positive about it, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
21
1
Order By: Relevance
“…Koskimäki (2005, p. 4) reported that in Finland two months prior to the introduction of the euro: '76% of the population thought that the introduction will raise the overall price level'. In Ireland, respondents in an interview study gave several reasons for believing that the introduction of the euro would lead to price increases: (1) prices in euros would be rounded up; (2) price rises would be hidden at the transition; and (3) there would be effects on the Irish economy of joining the Eurozone (Ranyard et al, 2005). Such expectations, then, could well have played a part in the rise in perceived inflation in Eurozone countries after the introduction of the euro.…”
Section: Expectationsmentioning
confidence: 99%
“…Koskimäki (2005, p. 4) reported that in Finland two months prior to the introduction of the euro: '76% of the population thought that the introduction will raise the overall price level'. In Ireland, respondents in an interview study gave several reasons for believing that the introduction of the euro would lead to price increases: (1) prices in euros would be rounded up; (2) price rises would be hidden at the transition; and (3) there would be effects on the Irish economy of joining the Eurozone (Ranyard et al, 2005). Such expectations, then, could well have played a part in the rise in perceived inflation in Eurozone countries after the introduction of the euro.…”
Section: Expectationsmentioning
confidence: 99%
“…The first part of the paper presents an overview of the results of an interview study conducted in Ireland (see Ranyard, Burgoyne, Saldanha, & Routh, 2005;Ranyard, Routh, Burgoyne, & Saldanha, 2007, for details), which aimed for an in-depth exploration of perceptions, feelings and experiences, and how these might have changed during the first year of adaptation to the euro. The broad aim of qualitative enquiry such as this is to elucidate 'the meaning of experience, actions and events as they are interpreted through the eyes of particular participants, researchers and (sub)cultures and ….…”
Section: Euro Stories: the Irish Experience Of A Change Of Currencymentioning
confidence: 99%
“…In real life consumers report having difficulties adapting to the euro (AaltoSetälä & Riajas, 2003;Cannon & Cipriani, 2003, Kirchler & Meier-Pesti, 2002Marques & Dehaene, 2004, Meier-Pesti & Kirchler, 2001Ranyard, Routh, Saldanha, & Burgoyne, 2005). Commonly, it has been found that consumers continue to convert from the euro to their old currency several months after the transition has taken place.…”
Section: Effects Of Nominal Representation Of Money: Empirical Findingsmentioning
confidence: 99%